Replacement name for the cicada genus Pycnoides Sanborn, 2020 (Hemiptera: Cicadidae: Cicadinae: Platypleurini) and sixteen new combinations - Sanborn, Allen F. (Zootaxa, 2020)
Dyticopycna nom. nov. pro Pycnoides Sanborn, 2020 nec Handianus (Pycnoides) Emelijanov, 1964 (Hemiptera: Cicadellidae: Deltocephalinae: Athysanini) is proposed. The species of Pycnoides Sanborn are transferred to Dyticopycna nom. nov. to become Dyticopycna antinorii (Lethierry, 1881) n. comb., Dyticopycna baxteri (Distant, 1914) n. comb., Dyticopycna becarrii (Lethierry, 1881) n. comb., Dyticopycna dolosa (Boulard, 1975a) n. comb., Dyticopycna hecuba (Distant, 1904) n. comb., Dyticopycna moniquae (Boulard, 2012) n. comb., Dyticopycna natalensis (Distant, 1905) n. comb., Dyticopycna neavei (Distant, 1912) n. comb., Dyticopycna passosdecarvalhoi (Boulard, 1975b) n. comb., Dyticopycna quanza (Distant, 1899a) n. comb., Dyticopycna semiclara (Germar, 1834) n. comb., Dyticopycna sylvia (Distant, 1899b) n. comb., Dyticopycna umbelinae (Boulard, 1975b) n. comb., Dyticopycna vitrea (Schumacher, 1913) n. comb., Dyticopycna vitticollis (Jacobi, 1904) n. comb., and Dyticopycna zambiaensis (Sanborn, 2020) n. comb.